Bacterial Spectrum and Antibiotic Sensitivity in open Fractures of the Extremities - Ahmad Zeb, Zulfiqar Ullah, Fahad Ullah, Arfa Safder, Yahya Khan, Uroosa Naseem, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Open fractures account for around 3 - 4% of all fractures, and infection caused by deprivation of bone and soft tissue, as well as loss of skeletal stabilization, is a serious consequence, particularly in grade III open fractures. Objective: To determine bacterial spectrum and antibiotic sensitivity in open fractures of the extremities Methodology: The current study was descriptive cross sectional study carried out at the department of Orthopedic Surgery, Khyber Teaching Hospital Peshawar for duration of six months from July 2021 to January 2022. All the samples were sent to the hospital diagnostic lab for bacterial identification and antibiogram assay. Kirby- Bauer method was used for antibiogram assay. The data was analyzed by using IBM SPSS version 19.0. Results: A total of 210 patients were included in our study. Male patients were 168(80%) and female were 42(20%). The major cause of fracture was traffic accident observed in 168 (80%) patients. Positive culture report was observed in 196 (93.33%) patients. Staphylococcus Aureus was most frequently observed in 115(54.76%) patients. High resistance against commonly used antibiotics was observed in our study. All the isolates were completely (100%) resistant to ampicillin. All the isolates were 100% sensitive to Amikacin except MRSA. Conclusion: Our study observed positive culture of bacteria in most of the open fractures of the extremities. Gram positive bacteria were most common than gram negative. Antimicrobial resistance was observed in majority of the bacterial isolates against commonly used antibiotics.